2020
DOI: 10.1007/s10163-020-01041-2
|View full text |Cite
|
Sign up to set email alerts
|

Recycled waste paper–cement composite panels reinforced with kenaf fibres: durability and mechanical properties

Abstract: There is a growing interest on recycling of waste fibres as an alternative to landfill disposal. The aim of the study was to investigate the durability and mechanical properties of waste paper-cement composite panels reinforced with varying kenaf fibre content (FC, 2-10%). The panels produced were evaluated for properties including modulus of rupture (MOR) and apparent modulus of elasticity (MOE). The resistance of the panels was tested in the field for both termite damage and fungi decay for a period of 24 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…At the same time, adding paper waste at a sufficient level into a composite material can improve the flexural strength of MBCs. This outcome is consistent with other research findings related to composite material studies that indicated that cellulose fiber reinforcement, particularly when it takes the form of recycled paper fibers, can function as reinforcement in composites [ 27 , 75 , 76 ]. This is because cellulose fibers provide added strength and elasticity, like more conventional reinforcing elements similar to fiberglass or carbon fibers [ 27 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…At the same time, adding paper waste at a sufficient level into a composite material can improve the flexural strength of MBCs. This outcome is consistent with other research findings related to composite material studies that indicated that cellulose fiber reinforcement, particularly when it takes the form of recycled paper fibers, can function as reinforcement in composites [ 27 , 75 , 76 ]. This is because cellulose fibers provide added strength and elasticity, like more conventional reinforcing elements similar to fiberglass or carbon fibers [ 27 ].…”
Section: Resultssupporting
confidence: 91%
“…composite material studies that indicated that cellulose fiber reinforcement, particularly when it takes the form of recycled paper fibers, can function as reinforcement in composites [27,75,76]. This is because cellulose fibers provide added strength and elasticity, like more conventional reinforcing elements similar to fiberglass or carbon fibers [27].…”
Section: Impact Strengthmentioning
confidence: 99%
“…The efficiency of the fiber matrix bond decreases with increasing fiber concentration, which is associated with a decrease in mechanical characteristics. Inadequate interfacial bonding hinders effective load transmission, which leads to rapid breakdown [48].…”
Section: Tensile Strengthmentioning
confidence: 99%
“…Based on their source, plant fibres were classified into: bast or stem fibres are obtained from the stalk of various dicotyledonous plants such as banana, jute, flax, ramie, kenaf, hemp etc; leaf fibres also referred to as hard fibres, extracted from the leaves of monocotyledonous plants like sisal, pineapple leaf etc; seed fibres derived from the seeds of plants includes cotton, kapok, oil palm, coir, etc (Mwaikambo, 2006). Several researchers determined the mechanical properties, water absorption, porosity and thermal analysis of the concrete casted using the plant fibres (Wafa, 2019;Arsene et al 2013;Amiandamhen, 2020). Among these plant fibres, Jute (Corchorus Capsularis), is a common vegetable fibre exhibit better mechanical properties and used in various industries for the production of new consumer goods (Sudhir et al 2011).…”
Section: Introductionmentioning
confidence: 99%